1992
DOI: 10.1159/000310261
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Surface Antigen in Tears and Aqueous Humor

Abstract: Tear samples of 20 patients who were determined to have positive hepatitis B surface antigen (HBsAg) after an acute hepatitis B infection and aqueous humor samples of 10 patients who were HBsAg carriers were tested for HBsAg, and the results obtained for serum and these fluids were compared. In 85% of the 20 patients who were HBsAg positive, HBsAg was found to be positive in tear samples. In 50% of the other 10 patients in aqueous humor was also found to be HBsAg positive. Our findings show that tears and aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Temel et al [1] noted that 7 of 10 HBsAg-seropositive patients also tested positive for HBsAg in tear and aqueous humor samples on the day of cataract surgery. Similarly, Koksal et al [2] found that 85% of HBsAg-positive patients also tested positive for HBsAg in tear samples. To our knowledge, the current study is the first to report detection of HBV in aqueous humor using PCR methodology.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Temel et al [1] noted that 7 of 10 HBsAg-seropositive patients also tested positive for HBsAg in tear and aqueous humor samples on the day of cataract surgery. Similarly, Koksal et al [2] found that 85% of HBsAg-positive patients also tested positive for HBsAg in tear samples. To our knowledge, the current study is the first to report detection of HBV in aqueous humor using PCR methodology.…”
Section: Discussionmentioning
confidence: 93%
“…Although no definitive cases have been published, it is plausible that HBV may be transmitted from infected patient to ophthalmologist via these media. A number of studies have reported the detection of HBsAg in tears and aqueous humor of HBsAg seropositive patients [1, 2]. Temel et al [1] noted that 7 of 10 HBsAg-seropositive patients also tested positive for HBsAg in tear and aqueous humor samples on the day of cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV can be detected in the eye as a number of studies have revealed hepatitis B surface antigen in tears and aqueous humor of hepatitis B surface antigen seropositive patients. 26 Researchers have also detected the presence of HCV RNA in tear fluid. 27 Uveitis might be a physiologic immune response to fight an infection within the eye.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that individuals with no clinical signs of HBV infection may be excreting virus in their tears. In 50% of HBV carriers, HBsAg was demonstrated in humor aqueous [13]. The presence of HBsAg in subretinal fluid was reported in a case of hepatitis B [14].…”
Section: Discussionmentioning
confidence: 99%